Autismo: déficit cognitivo ou posição do sujeito? - Paula Ramos Pimenta (2003)
The author proposes to review the concept of autism up to this day in terms of the ethiology, diagnosis criteria and treatment thereof. Following this investigative line, the area of study has been divided into two subareas: medical and psychoanalitical. In the medical field, a plurality of ethiological hypothesis can be found, still to be confirmed, exposing the scientific ignorance about the origins of autism. The diagnostic is phenomenological, being based on descriptions of observable behaviors without further support from complementary laboratory test which could back it up. The prescribed treatment is focused on education aided by secondary ones. Psychoanalisis, with its structural conception of the subject, places the ethiology of autism in the absence of the Ego Ideal, the symbolic element that represents the child in the desire of the mother. The diagnosis is performed under Transference but also taking the observable behaviors of the child into account. The author tries to make the most recent contributions of Lacan´s psychoanalisis for the guidelines of autism treatment known, concluding this work with a critical evaluation of medical and psychoanalitical propositions for these interventions.